(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
In the study principal component analysis and gene set enrichment analysis was carried out to evaluate genome wide expression and identify functional gene sets affected in peripheral blood mononuclear cells of patients with post-traumatic stress disorder and animal models of the disease. The results obtained indicate the significance of the genetic component in the pathogenesis of post-traumatic stress disorder, and provide strong evidence for the involvement of chronic inflammation, neuronal and cytokine/growth factor signaling pathways, in disease development and progression. In addition, the results obtained demonstrated that combination of principal component analysis with gene set enrichment analysis is an efficient strategy for discrimination of phenotype related gene expression variability from other factors.